Broadcast news writing, reporting, and producing - White, Ted 1926- (Elsevier/Focal Press, 2005)
Everyday essentials for news reporters, writers, assignment editors, and producers!
Includes index. - Includes bibliographical references and index. - Print version record
Keywords: Broadcast journalism; Reporters and reporting; Report writing; Presse audiovisuelle; Rapports; Rédaction; LANGUAGE ARTS & DISCIPLINES; Journalism; Omroep; Radio; Televisie; Journalistiek; Schrijven; Berichtgeving; Nieuws; Nieuwsprogramma's